6b-10=2(b-11)+4(b-2)

Simple and best practice solution for 6b-10=2(b-11)+4(b-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6b-10=2(b-11)+4(b-2) equation:



6b-10=2(b-11)+4(b-2)
We move all terms to the left:
6b-10-(2(b-11)+4(b-2))=0
We calculate terms in parentheses: -(2(b-11)+4(b-2)), so:
2(b-11)+4(b-2)
We multiply parentheses
2b+4b-22-8
We add all the numbers together, and all the variables
6b-30
Back to the equation:
-(6b-30)
We get rid of parentheses
6b-6b+30-10=0
We add all the numbers together, and all the variables
20!=0
There is no solution for this equation

See similar equations:

| 16y-24=-18+9y | | 2x^2-4=30 | | -7/8z=-1/5 | | 25x+21=-15(8x-25)-2x | | x/3-45=2x | | h+8=-27 | | x/3=45-2x | | 12.9x=16 | | (x2+5)-6=(9x+18)3 | | 2x-8=x+59 | | 5y+7=-14+8y | | 4(-8+5)=32x=26 | | 8(3x-7)=-6(x+7) | | -2x^2+52x+240=0 | | 5m−m=8 | | -2-8r=-8-2r | | x-7+3=5 | | -3(23x+6)=-26 | | 3(2+8b)-5(-6b+7)=79 | | 6x-2+2x=-2+4x+8 | | 30+15x=165 | | 2/7y-5/61=1/6-5/7y= | | z5− -14= 18 | | 15(x-13)=495 | | −3(23x+6)=−26 | | 5x+2=127x= | | 15(x-13)=12 | | 2x-3=x+62 | | k-2/2=2 | | 53-2/3j=59 | | 2/7y-5/6=11/6-5/7y | | v+1/3=2 |

Equations solver categories